Perception and Behavior of Forest Resources in Sukamaju Village Cihaurbeuti District Ciamis Regency - Irfan Rifani; Muhamad Isa Ramadhan (Jurnal Pendidikan Geografi Gea, 2022)
Perception affects the environmental behavior of forest resources. This study aims to determine the effect of perceptions on the environment behavior of forest resources in Sukamaju Village, Cihaurbeuti District, Ciamis Regency. The research method uses a moderating variable regression model. The research subjects are the people living around the forest area, categorized based on their work background. The results showed that the perception would increase along with the ongoing learning process. The longer the study, the more preference for decision-making in the use of forest resources. Besides being influenced by perception, behavior is also influenced by determinants of the physical and social environment, which predominantly work as a moderating variable that can weaken and strengthen the influence of perception on behavior. Working as a socio-cultural behavior will have implications for the level of individual and community interests collectively in the utilization of forest resources. The higher the intensity of dependence and use of forest resources, the more likely it affects the consistency of perceptions and behavior due to occupation factors. Based on this, the work strengthens the effect of perception on the environmental behavior of forest resources.